A new miniature species of Characidium Reinhardt (Ostariophysi: Characiformes: Crenuchidae) from the headwaters of the rio Araguaia, Brazil - Netto-Ferreira, André L.; Birindelli, José L. O.; Buckup, Paulo A. (Zootaxa, 2013)
Characidium mirim is described from the rio das Mortes, rio Araguaia basin in Central Brazil. The new species is distin-guished from its congeners by having an incomplete lateral line, a conspicuous dark longitudinal stripe and dark transverse bars not extending ventrally to the lateral line, and by lacking the adipose fin and the dark caudal blotch. A phylogenetic hypothesis based on the available data on the phylogenetic relationships of the subfamily Characidiinae is presented. Re-sults suggest that the new species is closely related to C. bahiensis, C. interruptum, C. lagosantense, C. nupelia, C. lanei, C. laterale, C. occidentale, C. orientale, C. rachovii, C. stigmosum, C. vestigipinne and C. xavante.